2018
DOI: 10.21608/adjalexu.2018.57570
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Gender on Child Dental Anxiety in a Sample of Egyptian Children (A Cross-Sectional Study)

Abstract: INTRODUCTION: Despite the recent developments in the dental equipment and treatment procedures, dental fear and anxiety (DFA) are relatively common among children and adults. Relating dental fear and anxiety to gender is a controversial issue in scientific literature. OBJECTIVES: The aim of this study is to examine the impact of gender on the child's dental anxiety in a sample of Egyptian children. MATERIALS AND METHODS: One hundred and twenty-six children 6-10 years old (60 boys and 66 girls), at the Departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…[16] Likewise, Gaber et al evaluated dental anxiety in 126 children aged 6-10 years and stated higher percentage of girls (30.5%) compared to boys (15.0%) were anxious. [17] In our study, dental anxiety was assessed using the FIS, and it was found that 48% of girls and 42% of boys indicated scores of 4 or 5, which did not differ significantly between the two groups in accordance with the studies indicating no significant relation between gender and dental anxiety. [18,19] Differences in methodology, sample size, and other factors can also influence the results obtained from different studies.…”
Section: Discussionsupporting
confidence: 85%
“…[16] Likewise, Gaber et al evaluated dental anxiety in 126 children aged 6-10 years and stated higher percentage of girls (30.5%) compared to boys (15.0%) were anxious. [17] In our study, dental anxiety was assessed using the FIS, and it was found that 48% of girls and 42% of boys indicated scores of 4 or 5, which did not differ significantly between the two groups in accordance with the studies indicating no significant relation between gender and dental anxiety. [18,19] Differences in methodology, sample size, and other factors can also influence the results obtained from different studies.…”
Section: Discussionsupporting
confidence: 85%
“…On the contrary other studies found that dental procedures were affected by the child gender where boys were less dentally anxious than girls which goes with the nature of boys who prefer to seem strong. [54,55]. However, Sharma et al [56] found that girls were more cooperative and responsive than boys, which was attributed to the quieter nature of girls.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this study is one of the first studies to examine the management of post-traumatic dental care anxiety in pediatric dental practice. In [ 28 ], the authors showed that girls are more dentally-anxious than boys. Yakar et al [ 29 ] reported high dental anxiety scores among women.…”
Section: Discussionmentioning
confidence: 99%